Infeksi Covid-19 pada Kehamilan dan Persalinan : A review - atmojo, joko tri (Jurnal Informasi Kesehatan Indonesia (JIKI), 2020)
Pneumonia caused by COVID-19 is very contagious, causing concern about intrauterine transmission from mother to fetus. The purpose of this review is to provide evidence-based information regarding the effect of COVID-19 on pregnancy and childbirth. This review was conducted by the author in March 2020, by searching databases including PubMed, Google scholar, and open access science direct. Based on studies reported in Wuhan and Iran, the symptoms experienced by pregnant women infected with COVID-19 are the same as women who are not pregnant. There was no possibility of transmission from mother to fetus during pregnancy. Symptoms of COVID-19 infection can affect the choice of labor.